Surface Study of Fe3O4 Nanoparticles Functionalized With Biocompatible Adsorbed Molecules - Lesiak, Beata; Rangam, N.; Jiricek, P.; Gordeev, I.; Tóth, J.; Kövér, L.; Mohai, M.; Borowicz, P. (Frontiers in Chemistry, 2019)
Surfaces of iron oxide of ferrimagnetic magnetite (Fe3O4) nanoparticles (MNPs) prepared by Massart’s method and their functionalized form (f-MNPs) with succinic acid, L-arginine, oxalic acid, citric acid and glutamic acid were studied by DLS, FTIR, UV-vis, TGA/DSC, X-ray photoelectron spectroscopy (XPS) and reflection electron energy loss spectroscopy (REELS). The XPS analysis of elements and their chemical states at the surface of MNPs and f-MNPs revealed differences in chemical bonding of atoms, content of carbon-oxygen groups, iron oxide forms, iron oxide magnetic properties, adsorbed molecules surface coverage and overlayer thickness, whereas the Auger parameters (derived from XPS and Auger spectra), elastic and inelastic scattering probabilities of electrons on atoms and valence band electrons (derived from REELS spectra) indicated modification of surface charge redistribution, electronic and optical properties. These modified properties of f-MNPs influenced their biological properties. The surfaces biocompatible for L929 cells showed various cytotoxicity for HeLa cells (10.8-5.3% of cell death), the highest for MNPs functionalized with oxalic acid. The samples exhibiting the largest efficiency possessed smaller surface coverage and thickness of adsorbed molecules layers, the highest content of oxygen and carbon-oxygen functionalizing groups, the highest ratio of lattice O2‑ and OH- to C sp2 hybridizations on MNPs surface, the highest ratio of adsorbed O‑ and OH- to C sp2 hybridizations on adsorbed molecule layers, the closest electronic and optical properties to Fe3O4 and the lowest degree of admolecule polymerization. This high cytotoxicity was attributed to interaction of surface with cells, where increased content of oxygen groups, adsorbed O- and OH- may play a role of additional adsorption and catalytic sites and a large content of adsorbed molecule layers carboxylic groups facilitating Fenton reaction kinetics leading to cells damage.